Efektivitas dan Validitas Modul Keanekaragaman Tumbuhan Berbasis Pemanfaatan Tanaman Obat Oleh Etnis Batak Sumatera Utara Sebagai Sumber Belajar Biologi Siswa Kelas X - Rizka Ramadani Dalimunthe; Khairuddin Khairuddin; Efrida Pima Sari Tambunan (Journal on Education, 2023)
The purpose of this study was to determine the development, validity and effectiveness of plant diversity modules based on the use of medicinal plants by the Batak ethnic group of North Sumatra as a source of learning biology for class X IPA students. The type of research is Research and Development using the design developed by Sugiyono through seven stages. The research instruments are validation sheets, trial questionnaires and learning achievement tests. The results showed that the percentage of final validation increased, namely material experts 98.96%, language experts 87.5%, media experts 81.25%, small-scale student responses 88.21%, large-scale student responses 89.68% and biology teacher responses 96.05% with very valid categories. The average N-Gain Score on small-scale and large-scale tests is 0.72 and the percentage is 72.17%, which is quite effective. So it can be concluded that the modules developed are valid and effective to be used as biology learning resources.